Analisis Pengaruh Luas Panen terhadap Produksi Beras Nasional : Pendekatan Regresi Linier Time Series - Mira Yanuarti; Anadiya Pingki; Dwita Prisdinawati; Fery Murtiningrum (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
Rice is the staple food of most Indonesian people, making its availability a national priority. This study aims to analyze the effect of harvested area on national rice production using a time series linear regression approach based on monthly data in 2025. The research employed quantitative methods using secondary data analyzed with SPSS 27. The regression results produced the equation Ŷ = –0.067 + 0.003X. The t-test showed a significance value < 0.001, indicating that harvested area has a positive and significant effect on rice production. The coefficient of determination (R²) was 0.994, meaning 99.4% of rice production variation is explained by harvested area. These findings indicate that fluctuations in national rice production are largely determined by changes in harvested area rather than short-term productivity variations. Therefore, policies to increase rice production should prioritize maintaining harvested area through land protection, planting acceleration, and crop failure mitigation. The study contributes to providing an empirical model for short-term prediction of rice production in Indonesia.